Development of an Efficient Compact Wideband Metamaterial Based Rectenna - SOBHAN SARAVANI (2023)
This thesis focuses on a design methodology for RF energy harvesting systems and far-field wireless powering of low-power devices. The energy harvesting system composed of an antenna which scavenges plane waves transmitted by the powering source, and delivers the captured RF power to a rectifying element. The generated DC power is used to empower low power devices independent of their electronic applications including IoT and wireless sensor nodes. For a quality energy harvesting system the role of antenna and rectifier are critical that work interactively for the optimum performance. To date, most works in the literature focus on the design of high gain antennas via traditional methods which requires large space area, thus, restricting their applications. Furthermore, there are only few broadband rectennas in the literature and most of them perform well only at the high power levels (i.e. 20mW). This PhD thesis focuses on design and implementation of a more reliable and practical energy harvesting system for space-restricted applications. To achieve this goal, a wideband and miniaturized zeroth-order resonance (ZOR) antenna loaded by parasitic element is presented. The measured operational bandwidth of the designed antenna is about 1.6 GHz from 1.715 to 3.318 GHz corresponding to 87.1% of the fractional bandwidth with excellent radiation efficiency up to 95.7%. Moreover, the design and implementation of a low power rectifier operating at 2.45 GHz with increased output tolerance is presented. The efficiency of the rectifier is maximized by properly terminating the harmonics generated by non-linear diode and reaches to 61.9% at 3 dBm power level. Additionally, design of compact dual output broadband rectifier is detailed, with the highest measured efficiency of 70.3%. At the very low input power level of -17 dBm, an efficiency better than 10% from 1.85 to 2.5 GHz is obtained. Several combination of rectifiers and antenna as well as compact integrated rectenna are designed, simulated and tested. It has been demonstrated that for a broadband rectenna, under multi-tone condition, the efficiency considerably improves and exceeds 50% at only 3.16 μW/cm2 while for the mono-tone case, the best recorded efficiency remains below 50% even at the power density level as high as 5.13 μW/cm2 for almost all measured frequency points. Measurement results clearly demonstrate the advantage of this broadband energy harvesting system and its potential for spacerestricted applications where the use of bulky and high gain antennas are impractical.